Gender-Aware and Place-Based Transitional Justice in Guatemala: Altering the Opportunity Structures for Post-Conflict Women's Mobilization. (June 2018) - Destrooper, Tine; Parmentier, Stephan
Place-based approaches to transitional justice, which foreground victim participation, have become increasingly popular in the last decade. The assumption is that these approaches enhance legitimacy, increase the local relevance of interventions, and empower victims. However, the causal mechanisms by which this alleged empowerment takes place, are not usually studied in great detail. This article examines whether altering the opportunity structures of (germinal) civil society organizations is one of the ways by which this empowering effect might take hold. The authors argue that in Guatemala, the transitional justice process, and in particular the truth commission, did indeed significantly alter the opportunity structures of grassroots indigenous women's groups, most notably by providing these groups with support to develop their own agenda and with access to 'elite allies'. Yet the fieldwork performed hitherto would also advise against treating localized and participatory approaches to transitional justice as a panacea, for even if a genuine bottom-up approach is promising, the ongoing institutionalization of the field of transitional justice makes adequate implementation of such an approach difficult; and especially in cases where victims face intersectional discrimination positive effects may be slow to materialize.